Comparative evaluation of the efficacy of occlusal splints fabricated in centric relation or maximum intercuspation in temporomandibular disorders patients - Marcelo Matida Hamata; Paulo Renato Junqueira Zuim; Alicio Rosalino Garcia (University of São Paulo, 2009)
Fabrication of occlusal splints in centric relation for temporomandibular disorders (TMD) patients is arguable, since this position has been defined for asymptomatic stomatognathic system. Thus, maximum intercuspation might be employed in patients with occlusal stability, eliminating the need for interocclusal records. This study compared occlusal splints fabricated in centric relation and maximum intercuspation in muscle pain reduction of TMD patients. Twenty patients with TMD of myogenous origin and bruxism were divided into 2 groups treated with splints in maximum intercuspation (I) or centric relation (II). Clinical, electrognathographic and electromyographic examinations were performed before and 3 months after therapy. Data were analyzed by the Student's t test. Differences at 5% level of probability were considered statistically significant. There was a remarkable reduction in pain symptomatology, without statistically significant differences (p>0.05) between the groups. There was mandibular repositioning during therapy, as demonstrated by the change in occlusal contacts on the splints. Electrognathographic examination demonstrated a significant increase in maximum left lateral movement for group I and right lateral movement for group II (p<0.05). There were no significant differences (p>0.05) in the electromyographic activities at rest after utilization of both splints. In conclusion, both occlusal splints were effective for pain control and presented similar action. The results suggest that maximum intercuspation may be used for fabrication of occlusal splints in patients with occlusal stability without large discrepancies between centric relation and maximum intercuspation. Moreover, this technique is simpler and less expensive.